Electronic properties and structure of single crystal perylene - Pookpanratana, Sujitra; Goetz, Katelyn (Organic electronics, 2018)
The transport properties of electronic devices made from single crystalline molecular semiconductors typically outperform those composed of thin-films of the same material. To further understand the superiority of these extrinsic device properties, an understanding of the intrinsic electronic structure and properties of the organic semiconductor is necessary. An investigation of the electronic structure and properties of single crystal α-phase perylene (C20H12), a five-ringed aromatic molecule, is presented using angle-resolved ultraviolet photoemission, x-ray photoelectron spectroscopy (XPS), and field-effect transistor measurements. Key aspects of the electronic structure of single crystal α-perylene critical to charge transport are determined, including the energetic location of the highest occupied molecular orbital (HOMO), the HOMO bandwidth, and surface work function. In addition, using high resolution XPS, we can distinguish between inequivalent carbon atoms within the perylene crystal and, from the shake-up satellite structure in XPS, gain insight into the intramolecular properties in α-perylene. From the device measurements, the charge carrier mobility of α-perylene is found to depend on the device structure and the choice of dielectric, with values in the range of 10−3cm2V-1s-1.
Gesehen am 08.05.2020